2000
DOI: 10.1021/jo991927o
|View full text |Cite
|
Sign up to set email alerts
|

4,4-Difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY) Dyes Modified for Extended Conjugation and Restricted Bond Rotations

Abstract: Five new, constrained, aryl-substituted 4,4-difluoro-4-bora-3a, 4a-diaza-s-indacene (BODIPY) dyes (3f,g and 4h-j) were prepared and investigated to see if they have more favorable fluorescence characteristics than the unconstrained systems 2 that were prepared in previous studies. Dye types 3 and 4 have relatively rigid conformations caused by the heteroatom (3f and 3g) or ethylene bridge (4h-j) linkers that preclude free rotation of the substituted-benzene molecular fragments. In the event, the new dye types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
136
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(142 citation statements)
references
References 18 publications
5
136
0
1
Order By: Relevance
“…Previous works pointed out that the inclusion of bulky groups with free rotation enhances the internal conversion processes, owing to the vibrational coupling, decreasing the fluorescence capacity of the dye. [13] However, in the present case, the bulkiness and disposition of the fluorene moieties, as well as their special proximity, leads to a high sterical hindrance, which should hinder their rotation and hence the non-radiative pathway. Such constrained structures are characterised by improved fluorescence capacities, [ 3d, 14] as is the present case of 1 d (Table 1).…”
Section: Fluorene-bodipy Derivativesmentioning
confidence: 72%
“…Previous works pointed out that the inclusion of bulky groups with free rotation enhances the internal conversion processes, owing to the vibrational coupling, decreasing the fluorescence capacity of the dye. [13] However, in the present case, the bulkiness and disposition of the fluorene moieties, as well as their special proximity, leads to a high sterical hindrance, which should hinder their rotation and hence the non-radiative pathway. Such constrained structures are characterised by improved fluorescence capacities, [ 3d, 14] as is the present case of 1 d (Table 1).…”
Section: Fluorene-bodipy Derivativesmentioning
confidence: 72%
“…Simple, alkyl-substituted dipyrrin BODIPYs, however, display absorption and emission bands with maxima only in the region of 480-540 nm so that today considerable effort is being made to shift the optical properties to the red. [5,[14][15][16][17][18] Several strategies have been reported to be successful such as the introduction of aryl substituents in the 3,5-and/or 1,7-positions of the BODIPY core (like in compounds 4, [19] 5, [20] 6, [21] 7, [22] 8 [23] and 9; [24] Scheme 2) or electron acceptors in the meso position, [25][26][27] aromatic ring fusion, [28][29][30] extension of the electronic p system by styryl substitution [31][32][33][34][35][36][37][38] or aza-substitution of the meso-carbon atom (like in compounds 7 and 9; Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…[4 -6] It has been reported that a modification of the π -conjugation of the molecules results in a redshift of their absorption and emission maxima, [7,8] whereas the introduction of a rigid conformation suppresses the non-radiative decay and resulting in high quantum yields. [9] Thus, structural details of functional dyes play an important role in their structure-function relationship. In this paper, we focus on the structural and conformational characterization of [bis-(N,N -difluoroboryl)]-3,3 -diethyl-4,4 ,8,8 ,9,9 ,10,10 -octamethyl-2,2 -bidipyrrin (1) by NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%